IDENTIFIKASI DAN KARAKTERISASI POTENSI AIR TANAH UNTUK PENGEMBANGAN IRIGASI SUPLEMENTER DI PABRIK GULA RENDENG DAN TRANGKIL JAWA TENGAH (IDENTIFICATION AND CHARACTERIZATION OF GROUND WATER POTENTIAL FOR DEVELOPING SUPLEMENTARY IRRIGATION IN ... - P. Rejekiningrum; F. Ramadani; Y. Apriyana; . Haryono (Agromet, 2005)
Micro sugar industry have some potential problem that needed serious interested, issues of global climate change have affected long drought period with the result that water availability for sugarcane very limited, and problem of land resources in specific location. To anticipate water scarcity in sugarcane plantation need to be optimalization water use through identification ground water potential to know depth and distribution groundwater resources used supplementary irrigation. This paper is attempt in optimalising water resources use through mapping of ground water to know ground water potencyl for developing supplementer irrigation with pumping and deep irrigation to increase sugar cane productivity, rendemen, and production in upland sugarcane PG. Rendeng and of Trangkil. Measurement of ground water characteristic through geolistrict survey using Terameter by detecting electrics into ground by electrodes and take the resistivity value in time dimension, this equipment can identify material underground more than 200 metre depth without passing drilling. Of underground material which have known, hence can be determined resistivity and aquifer thickness. The results of this research showed that in PG. Rendeng and and Trangkil have moderate ground water potency (overburden thickness 6-15 and aquifer thickness 16-25 m) until good (overburden thickness 16-25 and aquifer thickness 26-35 m) but moderate is to be dominant. Ground water potency is distribute in the middle and east of PG. Rendeng and Trangkil.